Awareness on Climate Resilient Technologies and their Adoption by Farmers of Palakkad and Wayanad District of Kerala State - T.P. Anseera and Jiju P. Alex (Indian Res. J. Ext. Edu., 2019)
Increasing incidences of climate change have negative consequences on agricultural production, especially in a state like Kerala which has shown consistent downward trends in area and production. The study analyzed the awareness of farmers on different climate resilient practices and their adoption. Study was conducted in Palakkad and Wayanad districts of Kerala with a sample of 100 farmers. It was found that 92.12 per cent of farmers had awareness on soil and water conservation measures followed by 80.22 per cent with awareness on agronomic practices and 7.27 per cent on institutional measures. Adoption of resilient practices also followed a similar trend, with as much as 81.6 per cent farmers adopting soil and water conservation practice, 72.52 adopting institutional measures and 69.14 per cent adopting prescribed agronomic practices. Rainwater harvesting, water recycling and addition of organic matter were known to all the farmers as effective climate resilient techniques. Awareness on use of breeds/ varieties suitable for climate change and high yielding, drought resistant forage crops production was found to be very low. Of the different climate resilient practices, rain water harvesting structures, integrated weed management practices and community seed bank were found to be adopted more. Farmers in Wayanad were found to have higher mean adoption index (82.83).